2017
DOI: 10.36251/josi.124
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of second generation Samoans in Australia

Abstract: Within this group are second generation Australians, who were born in Australia or New Zealand, but whose parent or parents were born in Samoa. Unfortunately, many second generation Australians of Samoan descent have not experienced the education and employment opportunities that prompted their parents' migration to Australia (Cuthill & Scull, 2011; Kearney & Glen, 2017). Instead, those with New Zealand citizenship, whose parents are unable to meet the qualifying criteria for permanent residence in Australia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Many of her study participants spoke less Samoan and relied on English to communicate. While these same language patterns could also be seen among our Samoan communities in Australia, for Samoan Australians whose first language was English, Stanley and Kearney (2017) identified that being around other Samoans and church attendance helped to "develop and maintain Samoan language" and "fa'a Samoa [the Samoan culture or way of life]" (p. 57).…”
Section: Negative Samoan Language Experiencesmentioning
confidence: 63%
See 1 more Smart Citation
“…Many of her study participants spoke less Samoan and relied on English to communicate. While these same language patterns could also be seen among our Samoan communities in Australia, for Samoan Australians whose first language was English, Stanley and Kearney (2017) identified that being around other Samoans and church attendance helped to "develop and maintain Samoan language" and "fa'a Samoa [the Samoan culture or way of life]" (p. 57).…”
Section: Negative Samoan Language Experiencesmentioning
confidence: 63%
“…With the languages of our Pacific cousins Niue and Tuvalu officially listed as endangered, studies on other ethnic groups in Australia, such as the Chinese community also show native language decrease among the second and third generation ("Endangered Languages: The Full List," 2011; Mak & Chan, 1995). There are also other international studies on second generation people that show the decline in native language use and the dominance of English (Alba et al, 2002;Portes & Rumbaut, 2001;Stanley & Kearney, 2017). According to Macpherson (1997), New Zealandborn Samoans are educated in a Palagi (Caucasian) system that constantly enforces the Palagi language (as cited in Akeripa, 2017).…”
Section: Negative Samoan Language Experiencesmentioning
confidence: 99%
“…One was based in Fiji and the other in South Auckland. As researchers from Pasifika communities, we advocate for the need to understand and embrace diasporic communities and different cultures, such as Pasifika, as it will assist in maximising sporting potential in general and benefit society overall (Stanley & Kearney, 2017;Zakus & Horton, 2009).…”
Section: Nurturing the Vā Of The Professional Sporting Spacementioning
confidence: 99%
“…Despite this change, many Samoan funeral traditions are continued in Australia. Samoans who reside in these countries still collectively mourn and support each other through a fusion of Fa'a Samoa with Christian hymns, si'i and traditional chanting, as shown in Figure 2 (see below) (Stanley & Kearney, 2017;Va'a, 1995).…”
Section: Samoan Perspectivementioning
confidence: 99%